Myokine Regulation of Insulin Secretion: Impact of Inflammation and Type 2 Diabetes - Ryan, Alexander J.; Ciaraldi, Theodore P.; Henry, Robert R. (Frontiers in Physiology, 2020)
Skeletal muscle (SkM) secretes factors (myokines) that can exert multiple actions. To study the control of myokine regulation of ß-cell function, SkM biopsies were taken from non-diabetic (ND) and Type 2 diabetic (T2D) subjects and satellite cells cultured to myotubes (MT). MT were also treated with lipopolysaccharide (infectious inflammation – II) or a combination of glucose (10 mM), insulin (120 pM), and palmitate (0.4 mM) (metabolic inflammation - MI) to model the inflammatory and metabolic conditions seen in vivo with T2D. Conditioned media (CM) was collected from MT after 24 hr and used to treat INS-1 cells for 24 hr. Cell viability, total insulin content, glucose-stimulated insulin secretion (GSIS) and maximal (IBMX-stimulated) IS (ISmax) were monitored. Under baseline conditions, CM from ND and T2D MT had no effects on INS-1 cell viability, insulin content, GSIS, or ISmax. After exposure to II, CM from ND-MT augmented GSIS in INS-1 cells by 100 ± 25% over control (p<0.05); T2D-CM had no effect. After exposure to MI, T2D-CM suppressed GSIS by 35 ± 5% (p<0.05); ND-CM was without effect. Under either of these conditions cell viability, total insulin content and ISmax were unaffected. Effects of CM on GSIS were lost after CM was boiled. Both augmentation of GSIS by ND-CM from II-treated MT, and suppression by T2D-CM from MI-treated MT, were inhibited by wortmanin, Ro 31-8220, and SB203580. In summary: 1) ND-MT are able to augment GSIS when stressed, 2) T2D-MT responding to a diabetic-like environment secrete myokines that suppress GSIS, 3) Unknown protein myokines exert effects specifically on GSIS, possibly through PI-3K, PKC, and/or p38 MAPK. In T2D, both insulin resistance and a suppression of adaptive increased insulin secretion are intrinsic properties of SkM that can contribute to the full T2D phenotype.